Pengaruh Ukuran Pemerintah Daerah, Leverage Dan Dana Perimbangan terhadap Kinerja Keuangan Pemerintah Daerah (Suatu Kajian Studi Literatur Manajemen Keuangan Daerah) - Henny A. Manafe; Simon Sia Niha; Dewa Putu S. Putra (Jurnal Ekonomi Manajemen Sistem Informasi, 2023)
Writing previous and appropriate scientific papers has an important role for writing subsequent scientific papers, especially regarding the influence of each variable or other variables. This scientific paper reviews the subject of a literature study on factors that affect local government financial performance, namely the size of local government, leverage, and balance funds. This scientific work is written by researchers so that they can determine hypotheses in determining hypotheses that result in variables so that they are useful for subsequent writing. The results obtained, such as: 1) The size of the local government has a positive and quite important impact on the financial performance of the local government; 2) Leverage has a positive and significant impact on the financial performance of local governments; 3) Balancing funds have a positive and significant impact on the financial performance of local governments; 4) The size of the local government, leverage, and balance funds have a positive and crucial effect simultaneously on the financial performance of the local government.